ANALISIS RESEPSI KHALAYAK TERHADAP OBJEKTIFIKASI PEREMPUAN DALAM SERIAL NETFLIX “Squid Game” - Karina Nabila Vanska Putri Sinulingga; Sunarto Sunarto; Hedi Pudjo Santosa (Interaksi Online, 2023)
Squid Game is a popular thriller film about a group of people who compete by risking their lives for the prize money of 45.6 billion won. This study aims to see how the objectification of women is shown in this film scene and how the audience interprets the scenes of objectification of women shown through various aspects of the film. This research is a qualitative research using audience reception analysis method from Stuart Hall which classifies audiences into 3 positions namely dominant position, negotiating position, and oppositional position. The main theories used are Cultural Studies Theory and Reception Theory. The results of this study are (1) there are six scenes which are then translated into eleven forms of objectification of women in accordance with the main concept of the theory of Cultural Studies, (2) The audience's interpretation of objectification in the Squid series mostly shows opposition or contra positions. This research is expected to be able to awaken filmmakers and the media to stop objectifying women in a mass media text, especially films in order to attract the attention of the audience.